The Fitness Cost of Fluoride Resistance for Different Streptococcus mutans Strains in Biofilms - Cai, Yanling; Liao, Ying; Brandt, Bernd W.; Wei, Xi; Liu, Hongyan; Crielaard, Wim; Van Loveren, Cor; Deng, Dong Mei (Frontiers in Microbiology, 2017)
The cariogenic bacterium Streptococcus mutans can develop stable resistance to fluoride through chromosomal mutations in vitro. Fluoride-resistant S. mutans has seldom been isolated in clinical settings, despite the wide application of fluoride in oral-care products. One explanation is that the fluoride-resistant S. mutans strains have decreased fitness. However, so far, there has been no conclusive evidence to support this idea. The aim of this study was to investigate the fitness cost of 48-h biofilms of two fluoride-resistant S. mutans strains, UF35 and UA159-FR (UAFR), using the wild-type fluoride-sensitive strain UA159 as a reference. The engineered UF35 strain contains one point mutation, whereas UAFR, selected from NaF-containing agar plates, has multiple chromosomal mutations. All biofilms were formed for 48 h under a constantly neutral pH or a pH-cycling (8 h of neutral pH and 16 h of pH 5.5) condition in the absence of fluoride. The biomass of the biofilms was quantified with a crystal violet assay. The biofilms were also treated with chlorhexidine or solutions at pH 3.0, after which their lactic acid production was quantified. Compared to the UF35 and UA159 biofilms, the biomass of UAFR biofilms was 2‒4 fold higher, and the UAFR biofilms were more resistant to chlorhexidine and low pH in terms of lactic acid production. No difference in biomass and lactic acid production was detected between UF35 and UA159 biofilms. The fluoride resistance of UAFR and UF35 strains in biofilms was further confirmed by treating the biofilms with NaF solutions. The level of NaF resistance of the three biofilms is generally ranked as follows: UAFR > UF35 > UA159. In conclusion, there is indeed a fitness consequence in UAFR, but surprisingly, this fluoride-resistant strain performs better than UF35 and UA159 under the described conditions. In addition, UF35 did not display a reduced fitness; it performed as well as the wild-type fluoride-sensitive strain.